2018
DOI: 10.4103/ijri.ijri_119_18
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory fossa depth: CT analysis of 1200 patients

Abstract: Background:Olfactory fossa (OF) is a depression in anterior cranial cavity whose floor is formed by cribriform plate of ethmoid. Lateral lamella, which forms its lateral boundary, is a thin plate of bone and is at risk of injury during functional endoscopic sinus surgery, especially when fossa is deep/asymmetric.Aims:To measure the variations in the depth of OF and categorize Kerala population as per Keros classification using computed tomography (CT).Settings and Design:This study was conducted in our institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 18 publications
3
16
4
Order By: Relevance
“…Again, this study has one of the largest case series in the literature. [9] Souza et al used the coronal plan on CT images in their study; the most common type 2 olfactory fossa (73.3%) was observed with the Keros classification in their cases, and similar to our study, they found the least type 3 olfactory fossa (0.5%). Also, a remarkable asymmetry has been achieved in the ethmoid roof height and contour.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Again, this study has one of the largest case series in the literature. [9] Souza et al used the coronal plan on CT images in their study; the most common type 2 olfactory fossa (73.3%) was observed with the Keros classification in their cases, and similar to our study, they found the least type 3 olfactory fossa (0.5%). Also, a remarkable asymmetry has been achieved in the ethmoid roof height and contour.…”
Section: Discussionsupporting
confidence: 89%
“…In Babu et al study, a statistically significant relationship was found between Keros type and gender, especially on the right side. [9] Although the rate of asymmetry in our study group was quite high (97.1%) compared to other studies, asymmetry was >1 mm in only 2.9% of cases. Finally, only seven subjects (1.3%) had different Keros type OFs on both sides, which was higher in Babu et al and Pawar et al [9,24] In the study conducted by Babu et al, the mean OF depth was 5.26±1.69 mm, which was slightly higher than in our study.…”
Section: Discussioncontrasting
confidence: 75%
See 3 more Smart Citations